MANAJEMEN MUTU PROGRAM KEPALA SEKOLAH DALAM MENINGKATKAN KEMAMPUAN LITERASI SISWA (Studi Kasus di SDN Angkasa 06 Margahayu Kabupaten Bandung) - R. Supyan Sauri; Teti Hartati; Entis Sutisman; Irma Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the quality management of the school principal’s literacy program in improving students’ literacy skills at SDN Angkasa 06 Margahayu, Bandung Regency. A qualitative approach with a case study design was employed to explore the planning, implementation, evaluation, follow-up actions, as well as challenges and solutions related to the management of the school literacy program. Data were collected through participatory observations, semi-structured interviews, and document analysis involving the principal and teachers. The data were analyzed using descriptive qualitative techniques through data reduction, data organization, and interpretative analysis. The findings reveal that the literacy program has been implemented in accordance with the Plan–Do–Check–Act (PDCA) quality management cycle; however, several aspects remain suboptimal. Program planning was not fully grounded in systematic literacy needs assessment, implementation encountered constraints related to teacher participation and supporting facilities, and evaluation activities tended to be administrative with limited evidence-based follow-up. Key challenges included limited human resources and inadequate literacy infrastructure. To address these issues, the principal adopted improvement strategies such as enhancing teachers’ professional capacity, optimizing literacy-related facilities, and strengthening collaboration among teachers, parents, and other school stakeholders. The study concludes that systematic, participatory, and sustainable quality management of school-based literacy programs is essential for improving elementary students’ literacy outcomes.